Where is Sociolinguistics now in the Philippines and What is its Direction - Pascasio, Emy M. (The Archive; 1983: Trends in Philippine Linguistics: Papers of the First Philippine Linguistics Congress, 2025)
Modern sociolinguistics of the past 10 years is viewed as a byproduct of very recent and still on-going developments in its two parent disciplines, linguistics and sociology. However, it would be but fair to say that more interest and greater attention have come from linguistics as a result of its recently more sophisticated synchronic concerns as well as its growing response to applied demands. Among those who consider themselves sociolinguists there is considerable conviction that their field is now making and will continue to make significant contributions to both parent fields. But then the true promise of the field will be realized only if a truly interdisciplinary work and thought will be fostered.